"Issues and trends in eco-tourism development in India" : national seminar proceedings, 6-7 January 2006, Thiruvananthapuram (Kerala Institute of Tourism and Travel Studies, 2006)
Proceedings of National Seminar on "Issues and Trends in Ecotourism Development in India."